2006
DOI: 10.1103/physreve.73.016133
|View full text |Cite
|
Sign up to set email alerts
|

Mutual attraction model for both assortative and disassortative weighted networks

Abstract: In most networks, the connection between a pair of nodes is the result of their mutual affinity and attachment. In this letter, we will propose a Mutual Attraction Model to characterize weighted evolving networks. By introducing the initial attractiveness A and the general mechanism of mutual attraction (controlled by parameter m), the model can naturally reproduce scale-free distributions of degree, weight and strength, as found in many real systems. Simulation results are in consistent with theoretical predi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…It has been reported that assortativity has substantial effect on dynamics on and of networks [12,21,22]. Although various kinds of models [23][24][25][26][27][28][29][30][31] have been proposed to uncover the underlying mechanisms of the emergence of 'scale-free' phenomenon, few works [11,[32][33][34][35] have been done to investigate how assortativity can arise in the evolution of network structure. In this paper, we study the intrinsic factors that can be attributed to the emergence of both assortative mixing and power law degree distribution of networked systems by considering a specific behavior in real social networks.…”
mentioning
confidence: 99%
“…It has been reported that assortativity has substantial effect on dynamics on and of networks [12,21,22]. Although various kinds of models [23][24][25][26][27][28][29][30][31] have been proposed to uncover the underlying mechanisms of the emergence of 'scale-free' phenomenon, few works [11,[32][33][34][35] have been done to investigate how assortativity can arise in the evolution of network structure. In this paper, we study the intrinsic factors that can be attributed to the emergence of both assortative mixing and power law degree distribution of networked systems by considering a specific behavior in real social networks.…”
mentioning
confidence: 99%
“…However, these evolution mechanisms just describe interactions between the newly added node and the old ones. Actually, such interactions also exist between old nodes in [20,21]. Furthermore, such interactions more easily occur between neighbors (friends of friends), so-called Triad Formation (TF) [22].…”
Section: Introductionmentioning
confidence: 97%
“…Recently, several weighted network models were proposed [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Classes of weighted network with fixed topological structures are proposed [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…But, these evolution mechanisms just describe interactions between the newly added node and the old ones. Actually, such interactions also exist between old nodes [19,20]. Moreover, such interactions more easily occur between neighbors, so-called Triad Formation [21][22][23].…”
Section: Introductionmentioning
confidence: 99%